Developing youths through health education for nation building (2011)
Healthy population of a nation is a valuable asset as it is the agent of nation building, the youths are important factor in the nation's developmental programme because of their abundant energy and numerical strength. Any nation aspiring for development must pay attention to the development of her youths. Nigeria as a developing nation must give priority to die youth developmental programme to prepare them properly and adequately for the leadership role of the future. The paper discussed concept and importance of health education as well as the role of health education in the development of health, intellect, value for life, good virtue and industry among Nigerian youths. It is recommended that, health education should form part of developmental programme for Nigerian youths.